Hope, death anxiety and simplified coping style scores of nursing students during the outbreak of COVID-19: A cross-sectional study. Issue 34 (27th August 2021) - Cheng, Linan; Guo, Xiaoyan; Liu, Haijing; Chen, Qian; Cui, Renshan
Abstract : Abstract: Nursing students are the main force of future nursing development, and their hope and death anxiety are important aspects of their coping styles and clinical practice. The present study examined the relationships between hope, death anxiety and simplified coping style scores of nursing students during the outbreak of COVID-19. Between February and April 2020, a cross-sectional descriptive study was performed using a Sojump online survey, and 870 nursing students completed the herth hope (HH), death anxiety scale (DAS) and simplified coping style questionnaire. The data were analyzed using t -tests, one-way analysis of variance (ANOVA), and multiple linear regression in SPSS 23.0 (IBM Corp, Armonk, NY). The average HH, DAS and active and passive coping scores of the 870 nursing students were 3.07 ± 0.32, 3.01 ± 0.37, 2.84 ± 0.48, and 2.25 ± 0.50, respectively. Participants with contact experience with individuals with suspected or confirmed COVID-19 were more likely to adopt passive coping styles than students without contact experience ( t  = 5.019, P  = .025). Being older and having higher inner positive readiness and expectancy, a lower inner sense of temporality and future, and lower time awareness were predictors of passive coping styles ( P  < .05). Living in cities (vs towns) and having a higher inner positive readiness and expectancy, a higher inner sense of temporality and future and lower cognition of death were predictors of active coping styles ( P  < .05). The findings of this study suggest that hope and death anxiety are important aspects of the coping styles of nursing students. Nursing educators should emphasize the role of hope, further deepen the death education mode, and perform scientific and reasonable death education programmes to reduce the death anxiety level of nursing students to promote their coping styles in crisis.